Income Tax Law = قانون الضرائب على الدخل (2025)
1. Range of the tax and its rate -- 2. Salaries and the like -- 3. Commercial and industrial activity -- 4. Non-commercial Professions revenues -- 5. Revenues of the real estate wealth -- Tax on Profits of juridical persons -- tax withheld at source -- Deduction, Collection and advance payments on account of the tax. -- Taxpayers' and others' Obligations -- Penalties -- Final Provisions.